2003
DOI: 10.1023/a:1025145331149
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The hypothesis that decreases in brain blood flow during respiration of hyperbaric oxygen result from inactivation of nitric oxide (NO) by superoxide anions (O2(-)) is proposed. Changes in brain blood flow were assessed in conscious rats during respiration of atmospheric air or oxygen at a pressure of 4 atm after dismutation of O2(-) with superoxide dismutase or suppression of NO synthesis with the NO synthase inhibitor L-NAME. I.v. administration of superoxide dismutase increased brain blood flow in rats brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…SOD increased CBF in rats breathing air, but was ineffective after previous inhibition of NOS 76 . HBO induced CBF decreases, though prior SOD prevented hyperoxic vasoconstriction and increased CBF under HBO in rats.…”
Section: Hyperbaric Oxygen (Hbo) and Cbf Regulation By Enosmentioning
confidence: 87%
See 1 more Smart Citation
“…SOD increased CBF in rats breathing air, but was ineffective after previous inhibition of NOS 76 . HBO induced CBF decreases, though prior SOD prevented hyperoxic vasoconstriction and increased CBF under HBO in rats.…”
Section: Hyperbaric Oxygen (Hbo) and Cbf Regulation By Enosmentioning
confidence: 87%
“…The vasodilator effect of SOD in HBO was not observed in rats pretreated with NOS inhibitor. These results suggest inactivation of NO by superoxide anion as a mechanism of hyperoxic vasoconstriction [76] .…”
Section: Hyperbaric Oxygen (Hbo) and Cbf Regulation By Enosmentioning
confidence: 99%
“…Other effects of HBO, including stimulation of angiogenesis [33,34,35,36], and decreased cerebral edema and intracranial pressure [16,37,38,39,40], have also been suggested as mechanisms of protection from cerebral ischemia. These recent studies have shown several pathways as possible targets for neuroprotection from HBO, although a good deal of the data is preliminary and needs to be replicated and expounded upon before a clear picture will arise as to the true mechanisms of HBO.…”
Section: Mechanism Of Action Of Hbomentioning
confidence: 99%
“…Moreover, eNOS may not be inhibited in the early period of exposure, although CBF decreased rapidly after the oxygen pressure was raised. As suggested by Demchenko et al and Zhilyaev et al this transient decrease was mainly resulted from inactivation of eNOS-dependent NO by •O 2 − , decreasing the basal vasorelaxing action of NO 17,18…”
Section: Discussionmentioning
confidence: 86%
“…However, it was different on the point that which NOS isoform played a more important role in the modulation of the later vasodilation. Some considered NO by eNOS was responsible for the development of hyperoxic hyperemia preceding O 2 seizures, whereas neuronal NO may mediate toxic effects of HBO mainly by its reaction with superoxide to generate the stronger oxidant, peroxynitrite 18. Others suggested late HBO-induced vasodilation depends upon NO produced by both eNOS and nNOS 5.…”
Section: Discussionmentioning
confidence: 99%